Penerapan Model Pembelajaran Student Facilitator And Explaining terhadap Hasil Belajar Siswa Kelas VIII SMP Negeri Purwodadi - Riska Dwi Putri Anjani; Ira Miyarni Sustianingsih; Sarkowi (Attractive : Innovative Education Journal, 2024)
This thesis is entitled "Application of the Student Facilitator and Explaining Learning Model to the Social Studies Learning Outcomes of Class VIII Students of Purwodadi State Middle School. "The formulation of the problem in this research is whether there is a significant increase in the Social Sciences Learning Outcomes of Class VIII Students of Purwodadi State Middle School after being given the Student Facilitator and Explaining Learning Model ?. This research aims to find out whether after implementing the Student Facilitator and Explaining model, the learning outcomes of class VIII students at SMP Negeri Purwodadi have improved. The type of research used is quasi-experimental. The population of all classes VIII of SMP Negeri Purwodadi and samples of class VIII.1 were taken randomly. Data collection was carried out using instrument tests in the form of multiple choice with 30 questions, pre-test-post-test in the form of multiple choice with 25 questions. The collected data was analyzed using the t-test at the significance level α = 0.05. Based on the results of data analysis, it can be concluded that the social studies learning outcomes of Class VIII students at Purwodadi State Middle School after implementing the Student Facilitator and Explaining learning model have seen significant improvements. The average student learning outcome was 83.86 and the percentage of students who completed it reached 92.85%.